CanASM: a comprehensive database for genome-wide allele-specific DNA methylation identification and annotation in cancer - Zhao, Jianmei; Zhao, Zeyu; Li, Hongfei; Yu, Haojie; Lin, Hao; Chen, Hanqi; Li, Xuecang; Liu, Di; Wang, Yiming; Wang, Guohua (BMC genomics, 2025)
Allele-specific DNA methylation (ASM) provides critical insights into the complex genetic and epigenetic mechanisms regulating gene transcription. Emerging evidence suggests that ASM is particularly enriched in gene enhancer regions, and recent studies have demonstrated that ASM is increased in cancer tissues compared with normal tissues. Despite the increasing recognition of ASM as a potential biomarker in tumorigenesis, systematic resources dedicated to identifying and annotating ASMs in cancer contexts remain limited. In this study, we developed CanASM ( https://bioinfor.nefu.edu.cn/CanASM/ ), the first comprehensive database specifically designed to identify and annotate ASM in cancer. In CanASM, ASM sites identified from bisulfite sequencing (BS-Seq) data across 31 cancer types and their matched normal tissue samples are cataloged. Importantly, CanASM includes extensive regulatory annotations for ASMs, including associated genes, cis-regulatory elements and transcription factor binding colocalizations, transcription factor affinity changes, etc. Users can query and explore ASMs using various parameters, such as single-nucleotide variations (SNVs), chromosomal coordinates, and gene names. The current version of CanASM includes 5,003,877 unique SNV-CpG pairs, including 3,056,776 index SNVs, of which 2,634,406 are single-nucleotide polymorphisms (SNPs), and 4,157,508 CpGs. With an intuitive interface for browsing, querying, analyzing, and downloading, CanASM serves as a valuable resource for researchers investigating cancer-associated genetic variations and epigenetic regulation in cancer.